Trade rationing of the sugar industry on the Left Bank of Ukraine in the late XIX – early XX centuries - Olianych, Valentina; Olianych, Larysa (My University, 2021)
The article is devoted to the study of sugar trade and its rationing by the state in order to increase sugar production in the Left-bank Ukraine in the late XIX-early XX centuries, as well as issues of wholesale and fair trade. The sugar industry is an important link in the country's economic life, so the author considers it necessary to study the processes of sugar production, and as a result, the trade processes that took place during the study period. In connection with the publication of the law on rationing sugar production (1895), significant changes are taking place in the sugar industry, which have increased the inflow of share capital. The government set annual marginal prices and regulated its entry into the domestic market. The limits set by this law regulated various price fluctuations within the country and thus created favorable conditions for the development of the sugar industry. Confidence in large profits attracted new investments in this industry and, as a result, the construction of new factories. The government regulation of the price of sugar also played a positive role in its sale: the sharp fluctuation in the price of sugar was stopped, prices steadily decreased during 1895-1914, and the consumption of this valuable food product increased.
Olianych V. Trade rationing of the sugar industry on the Left Bank of Ukraine in the late XIX – early XX centuries / Valentina Olianych, Larysa Olianych // Knowledge, Education, Law, Management, 2021. – № 4(40). – Vol. 2. – P. 63–67.
Keywords: цукрова промисловість, торгівля, цукор, ярмарки, ціна, нормування, якість; sugar industry, trade, sugar, fairs, price, rationing, quality